Understanding social capital in community‐driven ride sharing: Lessons from a developing country - Santa, Mijalche; Ciunova-Shuleska, Anita; Palamidovska Sterjadovska, Nikolina (Wiley, 2024)
This paper aims to analyze the dynamics of social capital within community‐based P2P ridesharing practices through the relational (trust), cognitive (shared meaning and identity), and structural (network of social ties) dimensions of social capital. 21 users of Facebook P2P ridesharing participated in three focus groups. Using reflexive thematic analysis, we identified the key themes around social capital dimensions and the main factors that impact social capital dynamics (social broker, social debriefing, and time pressure). The impact of the social broker on social capital dynamics in ridesharing activities via Facebook can be explained by creating new bridging capital through linking different online and offline networks (inter‐network bridging) and by strengthening bonding capital through linking ridesharing group members (intra‐network bridging). Negative social debriefing weakens bonding capital and creates new bridging capital, whereas positive social debriefing strengthens bonding capital. Under high time pressure, travelers engage in activities that foster bridging capital development, whereas, under low time pressure, they rely on their bonding capital, avoiding engaging in bridging capital. We provided a comprehensive understanding of the factors influencing social capital dynamics that further influence P2P ridesharing practices, thus improving the current theory on social capital dynamics.